Starch Hydrolysis, Polyphenol Contents, and In Vitro Alpha Amylase Inhibitory Properties of Some Nigerian Foods As Affected by Cooking - Saidu, Sani; Eleazu, Chinedum Ogbonnaya; Ebuka, David; Ikechukwu, Anthony; Blessing, Montalto; Chibuike, Nwoye; Chukwuma, Chukwu (Frontiers in Nutrition, 2017)
The effect of cooking on starch hydrolysis, polyphenol contents and in vitro α-amylase inhibitory properties of mushrooms (two varieties-Russula virescens and Auricularia auricula-judae), sweet potato (Ipomea batatas) and potato (Solanum tuberosum) was investigated. The total, resistant and digestible starch contents of the raw and cooked food samples (FS) ranged from 6.4 to 64.9; 0 to 10.1; and 6.4 to 62.7 g/100 g respectively while their percentages of starch digestibility (digestible starch values expressed as percentages of total starch hydrolyzed) ranged from 45.99 to 100. Raw and boiled unpeeled potato, raw and boiled peeled potato, raw A. auricula-judae and sweetpotato showed mild to high α-amylase inhibition (over a range of concentration of 10 to 50 mg/ml) which was lower than that of acarbose (that had 69% inhibition of α-amylase over a range of concentration of 2 to 10 mg/ml), unlike raw R. virescens, boiled A. auricula-judae and boiled sweet potatoes that activated α-amylase and boiled R. virescens that gave 0% inhibition. The food samples contained flavonoids and phenols in addition. The significant negative correlation (r = -0.55; p = 0.05) between the α-amylase inhibitory properties of the raw and cooked food samples versus their SD indicates that the α-amylase inhibitors in these food samples also influenced the digestibility of their starches. In addition, the significant positive correlation between the α-amylase inhibitory properties of the raw and cooked food samples versus their RS (r = -0.59; p = 0.01) contents indicates that the RS constituents of these food samples contributed to their α-amylase inhibitory properties. The study showed the usefulness of boiled unpeeled potato, boiled potato peeled and raw sweet potato as functional foods for people with type 2 diabetes